Uncovering Language in Business Communication Space: Variation between Formal and Informal Language in Mandailing Natal - Junita Irawati (PT Agung Media Publisher, 2024)
This research delves into the intricate dynamics of formal and informal language usage within the realm of business communication in Mandailing Natal. Mandailing Natal, characterized by its cultural and linguistic diversity, serves as a distinctive backdrop for comprehending the nuanced role of language in business interactions. Employing a method of language variation analysis, this study scrutinizes various business communication texts, including formal letters, emails, and face-to-face conversations. The objective is to unravel the disparities in the utilization of formal and informal language. The findings of the research reveal that within the business communication space, the deployment of formal and informal language not only mirrors organizational hierarchy but is intricately linked to the local cultural context. Formal language predominantly governs official documents and written communication, while informal language prevails in face-to-face interactions and everyday situations. Furthermore, language variation extends to the incorporation of local dialects and distinctive expressions unique to Mandailing Natal, contributing cultural richness to business communication.